Phonoaudiological interventions in maternal breast-feeding of parity zero mothers - Madureira Pivante, Cristiane; Monteiro Correia Medeiros, Andréa (O Mundo da Saúde, 2006)
This work has as its aim to investigate the effectiveness of the together maternal breast-feeding of parity zero mothers. Having as study point the phonoaudiological and general orientações given by the phonoaudiology team of the Neomater Hospital and Maternity. The maternal reaction to the newborn and the mother’s behavior during the breast-feeding act determine the type of approach orientations given should have in order to make mothers awareof the importance of breast-feeding as a factor in the develo- pment of the sensory-motor-verbal functions. Breast-feeding was considered successful when we were able to observe the newborn sucking the mother’s breast in a organized way, something that happened in 97% of the mothers of babies interned in the maternity and we can conclude that the orientations as well as the interventions of the professional had been enlightening, reducing doubts and apprehensions regarding the breast-feeding situation.